Patients' Knowledge Description of Range of Motion (ROM) Implementation in Stroke Disease at the Neurology Outpatient Clinic of RSUD Syekh Yusuf Gowa - Asriani Bahar (Jurnal EduHealth, 2023)
Stroke is a clinical syndrome characterized by a sudden, rapidly progressive onset of focal and/or global neurological deficits, lasting 24 hours or more, or resulting in immediate death, solely caused by non-traumatic cerebral blood circulation disorders. This study employs a descriptive research design with data collection using a questionnaire. The sample consists of 30 respondents, anyone coincidentally encountered by the researcher can be used as a sample, considering those encountered coincidentally as a data source. The conclusion drawn from 30 respondents in the neurology outpatient clinic of RSUD Syekh Yusuf Gowa indicates that 4 individuals or 13.3% of respondents have good knowledge, 17 individuals or 56.7% have sufficient knowledge, and 9 individuals or 30.0% have insufficient knowledge. Therefore, the knowledge of patients regarding the implementation of Range of Motion (ROM) in patients with stroke needs improvement by relevant health authorities.